AB1067 THE IMPACT OF ACUTE RHEUMATIC FEVER IN A PROVINCE OF CENTRAL-NORTH ITALY. (June 2019) - Tronconi, Elena; Miglionico, Erika; Donti, Andrea; Pession, Andrea; Miniaci, Angela
Abstract : Background: Acute rheumatic fever (ARF) is a multisystem complication of group A streptococcal (GAS) infection. The incidence of ARF varies greatly in different geographic areas, with the highest incidence in Asia, Eastern Europe, and Australia (10-350 out of 100 000 per year) (1) and lowest (0.5-3 out of 100 000) in the US and Western Europe. In 2015 the latest version of Jones Criteria has been published (2), incidence less than 2 out of 100.000 per year was established to define low-risk (LR) population. Due to the lack of nationwide epidemiologic data in Italy, it is difficult to define the correct population Jones criteria's category to use. Objectives: To estimate the incidence of ARF in a metropolitan area of Central-North Italy and to study the clinical characteristics of the disease in a developed country. Methods: We retrospectively analyzed the data of all patients with ARF aged 5-14 years old, diagnosed according to the classical and now LR Jones criteria (2), referred to Sant'Orsola-Malpighi Hospital of Bologna from January 2012 to December 2017 living in the province of Bologna. Results: We identified a total of 24 patients diagnosed by ARF. In the province of Bologna, the inhabitants between 5 and 14 years of age varied from 82.967 in 2012 to 89.699 in 2017. Every year the annual incidence of ARF was above 2 out of 100.000. The highest incidence was reported in 2013 with 8 new diagnosis (incidence of 9.3 out of 100 000 per year). Carditis was present in 20 patients (83.3% of cases), chorea in 8 children (33.3%). Only 3 patients presented polyarthritis at diagnosis while 9 had polyartralgia and 3 presented with monoarthritis. In 6 patients the diagnosis followed the onset of chorea and no joint involvement was recorded. In 5 patients the diagnosis of ARF was made after the detection of classical cardiac findings without other major criteria. Cardiac involvement was characterized by mitral regurgitation in 17 cases and aortic regurgitation in 10 (8 patients with mitral aortic involvement). Five patients presented with fever (≥38.5°C), 11 children had elevated inflammatory markers as erythrocyte sedimentation rate (ESR) ≥ 60 mm/h and/or C-reactive protein (CRP) ≥3.0 mg/dL. Only 5 patients had positive swab for GAS. Twelve patients (50%) were treated with steroid. Fourteen patients received secondary prophylaxis every 28 days, two of them switched to every 21 days. Conclusion: Our study confirms the previous published data of Breda et al . (3) and Licciardi et al . (4) in other Italian areas supporting the evidence for high risk (HR) in our region. Furthermore, this study shows that in our population only few patients had the classical polyarthritis presentation. It is important to consider the new HR criteria for arthritis in order not to miss diagnosis. A careful clinical history is needed because the demonstration of GAS infection is often difficult. These data may strengthen the hypothesis to consider our whole country as a HR area for ARF. A nationwide study is mandatory. References: [1] Carapetis J, McDonald M, Wilson N. Acute rheumatic fever. Lancet 2005;366:155-68. [2] Gewitz H, Baltimore R, Lloyd T, Craig S, Stanford S, Carapetis J. Revision of the Jones Criteria for the diagnosis of acute rheumatic fever in the era of Doppler echocardiography: a scientific statement from the American Heart Association. Circulation 2015;131:1806-18. [3] Breda L, Marzetti V, Gaspari S, Del Torto M, Chiarelli F, Altobelli E. Population-based study of incidence and clinical characteristics of rheumatic fever in Abruzzo, central Italy, 2000-2009. J Pediatr. 2012 May;160(5):832-6.e1. [4] Licciardi F, Scaioli G, Mulatero R, Marolda A, Delle Piane M, Martino S, Montin D, Tovo PA. Epidemiologic Impact of the New Guidelines for the Diagnosis of Acute Rheumatic Fever. J Pediatr. 2018 Jul;198:25-28.e1. Disclosure of Interests: None declared